Shakespeare in ten acts - McMullan, Gordon, 1962- $e editor; Wilcox, Zoë $c (Curator) (London :, 2016)
Four hundred years after Shakespeare's death, it is difficult to imagine a time when he was not considered a genius. But those 400 years have seen his plays banished and bowdlerized, faked and forged, traded and translated, re-mixed and re-cast. Shakespeare's story is not one of a steady rise to fame; it is a tale of set-backs and sea-changes that have made him the cultural icon he is today. This revealing new book accompanies an innovative exhibition at the British Library that will take readers on a journey through more than 400 years of performance. It will focus on ten moments in history that have changed the way we see Shakespeare, from the very first production of Hamlet to a digital-age deconstruction. Each performance holds up a mirror to the era in which it was performed. The first stage appearance by a woman in 1660 and a black actor playing Othello in 1825 were landmarks for society as well as for Shakespeare's reputation. The book will also explore productions as diverse as Peter Brook's legendary A Midsummer Night's Dream, Mark Rylance's 'Original Practices' Twelfth Night, and a Shakespeare forgery staged at Drury Lane in 1796, among many others. Over 100 illustrations include the only surviving playscript in Shakespeare's hand, an authentic Shakespeare signature, and rare printed editions including the First Folio. These - and other treasures from the British Library's manuscript and rare book collections - feature alongside film stills, costumes, paintings and production photographs.